Impact of Emotional Intelligence on Academic Achievement of English Language Learners - Muhammad Umar Farooq, Kamran Riaz, Choudhary Zahid Javid (JSSH, 2023)
Among different learning concepts and models in psychology, EI is progressively being infused in teaching, education and development. Although students are equipped with books, notebooks, pens and pencils while teachers have course books, charts, blackboard, reference books and other teaching resources, most of the time students cannot meet the standards of learning. The purpose of the present research is to find out the relationship between emotional intelligence and academic success of the university students (enrolled in MA English) and important gender differences on academic success. Bar-On Emotional Intelligence Quotient Inventory of 125 items (Bar-On EQ-i: 125) was used to collect the data from 60 university graduates.